A cost-effective approach to introduce an optical WDM network in the metropolitan environment. - Johansson, S.
A case study shows that an optical wavelength division multiplexing (WDM) network can be employed in a metropolitan network in a cost effective way. In part, cost savings are realized due to the total number of line terminals required and the fact that the dimensions of the electrical nodes decrease when exploiting optical cross connects (OXCs) to a large extent. Optical WDM rings are also an important building element when designing a metropolitan network. A number of the properties of WDM rings are classified, resulting in eight different ring architectures. Additional requirements arise when considering ring-to-ring connections. The extent of the rings chosen for the case study is validated from the transmission point of view by a simple model. Finally, as an alternative to an all-optical approach, an opto-electrical approach is presented
Keywords: All-optical approach; Cost savings; Cost-effective approach; Electrical nodes; Line terminals; Metropolitan network; Optical WDM network; Optical WDM rings; Optical cross connects; Opto-electrical approach; Ring architectures; Ring-to-ring connections; Wavelength division multiplexing